Chemical compound and degree of its contamination as the basis to systematization of post-consumer wood - Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2008)
Chemical compound of post-consumer wood and degree of its contamination has been analysed beginning with treatment of raw material and wooden materials on the different processing stages up to removal of the finished products (and wastes that could be used) within different entities of management. The compound and substance of the contaminators of post-consumer wood have been studied in detail, especially based on wood preservation characteristics such as fire-retardant, wood preservative, insecticide, fungicide, biocide, fixing agents, and other chemicals. It has been developed a classification of foreign bodies in post-consumer wood covering mechanical and chemical stained agents. The most dangerous substances, carcinogenic compounds and toxic components which can be found in post-consumer wood have been described, in particular pentachlorophenol, lindane, permethrin, dichlorodiphenyl-threechloretan (DDT), polychlorinated biphenyls (PCB), polychlorinated terphenyls (PCT), polybrominated biphenyls (PBB), polyvinilcloruro (PVC), and oils that are produced by fractions of coal tar (benzopyren) and compounds which contain benzo(a)pyren and other superficially active hydrocarbons (SAH) and others. It has been suggested a classification of post-consumer wood based on the degrees of contamination. Based on detailed analysis it has been grounded the four groups of post-consumer wood which meet the international systems of classification of similar wastes. The list of the most widespread post-consumer wood wastes has been systematized in terms of groups, species, sub-species, categories and codes. The list of dangerous components of wastes has been generalized covering the following chemical elements (arsenic, boron, cadmium, copper, mercury, lead, titanium, fluorine, chlorine, chromium, zinc and others) and their compounds. It has been presented a limited range for wood dust and chips which are used for producing of wooden boards. The criteria of classification of post-consumer wood (possible concentrations of harmful components) have been offered for the different types of incineration.